Bibliometric analysis of 100 most cited papers on oral proliferative verrucous leukoplakia - Namrata Sengupta; Gargi S. Sarode; Sachin C. Sarode (Journal of Oral Biology and Craniofacial Research)
Background: Bibliometric analysis of highly cited papers in a particular discipline brings forward the impactful papers published, the significant journals and the researchers in the field. These studies help in identifying research trends and research lacunae in the field, thus guiding the future research works. Oral proliferative verrucous leukoplakia (OPVL) is a challenging lesion with no uniform diagnostic criteria. Thus, bibliometric analysis of published papers in this field will help researchers and clinicians to get an overview of the research trends and the research lacunae associated with OPVL. Method: A search was done with help of Scopus database in November 2023. The articles on OPVL were retrieved and reviewed thoroughly. The bibliometric data was also recorded. Results: The impactful research papers were published in the time span of 1985–2022 with maximum output being in the decade 2011–2020. The highest citation received was 297 and the least was 4 (mean citations 34 ± 42.57). These papers were published in 47 different journals. Seven authors contributed 5 or more papers each. United States had the major contribution of papers (n = 28). There were 71 articles and 18 review papers in the top list. Conclusion: This bibliometric and citation analysis of OPVL research papers will guide researchers and clinicians in understanding the research traits and thus, may help in making OPVL a less challenging lesion.